Assessment of Urokinase Plasminogen Activator Receptor (uPAR) in Nephropathy Type 2 Diabetic Patients with Microalbuminuria - Alkubaisi, Mithal R.; Elias, Noor Ghassan; ALShaban, Sahar Abdul Wahab; Salman, Abrar Dawood; Tahir, Noor Thair; AlAbdaly, Abdilya R. (Iraqi Journal of Science, 2025)
The glycosylphosphatidylinositol (GPI)-anchored receptor, known as the urokinase plasminogen activator receptor (uPAR), may serve as a valuable marker for the diagnosis and prognosis of sepsis, critical illnesses, and a range of inflammatory diseases. This study examines the impact of uPAR on clinical parameters in patients with type 2 diabetes and microalbuminuria. A total of 90 participants were enrolled in a case-control design, comprising 50% diabetic individuals with microalbuminuria and the remainder being healthy individuals aged range (35-63) years. Clinical parameters, along with demographic data, were collected from participants between November 2023 to January 2024. These parameters included age, body mass index, fasting blood sugar, haemoglobin A1C (HbA1C), lipid profile, urea, creatinine, and most importantly uPAR. Using an independent samples test with a significant level of 0.05, our experiment revealed that there was a significant difference between diabetic patients and healthy individuals when it comes to clinical parameters, p-value < 0.001. All clinical parameters were shown to be higher in diabetic patients with microalbuminuria compared to healthy individuals, except for high-density lipoprotein. An increased level of uPAR in patients with type 2 diabetic and microalbuminuria may be considered an effective biomarker for the early diagnosis of diabetic nephropathy, which is associated with a higher risk of complications of the disease, especially to cardiovascular diseases